Sirt1 overexpression attenuates Western‐style diet‐induced aortic stiffening in mice. Issue 9 (13th May 2022) - Gogulamudi, Venkateswara R.; Machin, Daniel R.; Henson, Grant D.; Lim, Jisok; Bramwell, Richard C.; Durrant, Jessica R.; Donato, Anthony J.; Lesniewski, Lisa A.
Abstract: Increased arterial stiffness is a cardiovascular disease risk factor in the setting of advancing age and Western diet (WD) induced obesity. Increases in large artery stiffness, as measured by pulse wave velocity (PWV), occur within 8 weeks of WD feeding in mice. Sirtuin‐1 (Sirt1), a NAD‐dependent deacetylase, regulates cellular metabolic activity and activation of this protein has been associated with vasoprotection in aged mice. The aim of the study was to elucidate the effect of global Sirt1 overexpression (Sirt tg ) on WD‐induced arterial stiffening. Sirt1 overexpression did not influence PWV in normal chow (NC) fed mice. However, PWV was higher in wild‐type (WT) mice ( p < 0.04), but not in Sirt tg mice, after 12 weeks of WD and this effect was independent of changes in blood pressure or the passive pressure diameter relation in the carotid artery. Overexpression of Sirt1 was associated with lower collagen and higher elastin mRNA expression in the aorta of WD fed mice (both p < 0.05). Although MMP2 and MMP3 mRNA were both upregulated in WT mice after WD (both p < 0.05), this effect was reversed in Sirt tg mice compared to WT mice fed WD (both p < 0.05). Surprisingly, histologically assessed collagen and elastin quality were unchanged in the aortas of WT or Sirt tg mice after WD. However, Sirt tg mice were protected from WD‐induced glucose intolerance, although there was no difference in insulin tolerance between groups. These findings demonstrate a vasoprotective effect of Sirt1 overexpression that limits the increase in arterial stiffness in response to consumption of a WD. Abstract : Sirt1 attenuated Western diet‐induced aortic stiffness.